Analisis Performa RouterOS MikroTik pada Jaringan Internet - Taufik Rahman; Sumarna Sumarna; Hafis Nurdin (P3M Politeknik Negeri Bengkalis, 2020)
The internet network enters various sectors and is used in various activities, especially in the automation, industry 4.0 trend. Where almost all applications, ranging from desktops, websites, mobile (android and ios) that are used in various fields of education, transportation, banks, logistics, services, of course use high complexity internet networks that need to be analyzed so that high performance can be obtained. Analyzing the performance of MikroTik on the internet is the aim of this research. Research by configuring includes ip route, firewall filter, NAT, Mangle for packet tagging, Queue (bandwidth management), bridge wireless, DHCP and ip cloud DDNS on MikroTik. The results concluded that moving the configuration center point on the modem (giving the IP address down) to the MikroTik router can be done well, it can also translate company, institutional, school and even parent policies to the home internet when children access the internet, such as when it is allowed to access the internet can be arranged, things that may or may not be arranged in order to educate children to use the internet positively, use MikroTik to analyze internet network performance. As for the further research by looking at problems that exist after MikroTik is configured.